Effect of spider silk on the foraging activity of Acrida turrita (Linnaeus, 1758) (Orthoptera: Acridinae). (3rd April 2019) - Tahir, Hafiz Muhammad; Khalid, Nimra; Hamza, Anum; Nadeem, Junaid
Abstract: Predators hold a position of great importance in agro-ecosystems. Their primary significance is that they deter the prey and reduce their plant foraging behaviour, thereby reducing damage and indirectly enhancing the biomass production. The present study was designed to observe the foraging activity of insects in response to spider silk and the cues deposited by spiders on the plants. Orb-weaving spider, Argiope trifasciata, was used as a silk source while Acrida turrita, the common grasshopper of rice fields was used as model herbivorous insect. Foraging of grasshoppers on the silk/cues-deposited plant leaves was compared with the control leaves. Resultantly, a sharp contrast was observed in the foraging activity. Silk-treated leaves were distinctly avoided by the grasshoppers when they were given a choice between the silk-treated and untreated leaves. Furthermore, the learning behaviour of grasshopper was also examined against fresh spider cues. The grasshoppers exhibited a preference for the clean filter paper; by spending more time on it as compared to the cue-deposited filter paper. Therefore, the study provided conclusive evidences that irrespective of the absence of spider, the presence of silk itself is an effective deterrent in threatening the prey and reducing the herbivory damage.